Fabrication and thermal stress analysis for PZT thin-layered structures - Zhang, Yun. (2008)
Multi-layered thin film structures with silicon as substrate are widely used in modern electronic industry as building blocks of micro devices and systems. When multiple thin film layers are deposited or grown on a silicon substrate, residual stresses are inevitably arisen inside the thin films due to thermal mismatch, phase transfer, and chemical reaction, etc. The residual stress induced cracking and damage is always the main concern in design and fabrication process of novel micro-mechanical devices, as these stresses frequently provide the driving force for mechanical and functional failure.